Human Development Index in Islamic Perspective in Mandailing Natal - Siregar, Erni Yusnita; Azizaturrahmah, Azizaturrahmah (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
The Human Development Index (HDI) is one of the indicators used to measure the social and economic progress of a region. However, in the Islamic perspective, human development is not only assessed from economic and social aspects alone, but also from spiritual and moral aspects. This article aims to analyze the Human Development Index (HDI) in Mandailing Natal in 2024, using a holistic Islamic perspective. This study shows that although the HDI in Mandailing Natal has increased, there is significant inequality in the aspects of social welfare and education. From an Islamic perspective, human development must include a balance between material and spiritual needs, which reflects a more just and prosperous quality of life.